Reversible Toxic Effects of the Dietary Supplement Indole-3-Carbinol in an Immune Compromised Rodent Model: Intestine as the Main Target. (4th May 2017) - Fletcher, Arnetta; Huang, Haiqiu; Yu, Lu; Pham, Quynhchi; Yu, Liangli; Wang, Thomas T. Y.
ABSTRACT: Dietary supplements are widely used in the United States, but the safety issue remains unresolved. Immuno-deficient or immuno-compromised patients, estimated to exceed 10 million in the United States, are known to use dietary supplements. This population potentially may be susceptible to supplements' adverse effects. The cruciferous vegetable-derived indole-3-carbinol (I3C) is known for its possible protective effects against a number of chronic diseases and is commercially available as a dietary supplement. However, the safety of orally consumed I3C in the general population and particularly in immuno-compromised individuals remains unknown. In this study, rodent model of immune-deficient male BALB/c nu/nu athymic mice were given diets supplemented with 0-100 μmoles I3C/g diet for 4 weeks. We found that BALB/c nu/nu mice were not viable after three days on a 100 μmoles I3C/g supplemented diet. Switching to the control diet (without I3C) after first detection of stress resulted in a 75% recovery of mice. Mice fed with 10-50 μmoles I3C/g supplemented diet survived but showed concentration-dependent adverse effects. More importantly, the intestine appeared to be the target of I3C toxicity. Number and width of intestinal villi were significantly altered by I3C, which associated with a dose-dependent reduction in cell proliferation and increase in apoptosis. Other molecular effects observed for I3C include activation of multiple xenobiotic metabolism pathways. This is the first study to report hazardous effects of I3C supplementation that are specific to the gastrointestinal tract in an immuno-compromised model and should serve as a caution in using I3C as dietary supplements.